The cellular microenvironment and cell adhesion: a role for O-glycosylation. - Zhang, L.; Ten Hagen, K.G. (Biochemical Society Transactions, 2011)
Glycosylation is one of the most abundant protein modifications in Nature, having roles in protein stability, secretion and function. Alterations in mucin-type O-glycosylation are responsible for a number of human diseases and developmental defects, as well as associated with certain types of cancer. However, the mechanistic role of this form of glycosylation in many of these instances is unclear. Here we describe how one glycosyltransferase responsible for initiating mucin-type O-glycosylation (PGANT3), specifically modulates integrin-mediated cell adhesion by influencing the secretion and localization of an integrin ligand. The integrin ligand Tiggrin, is normally O-glycosylated and localized to the basal matrix, where adhesion of two opposing cell layers takes place. In pgant3 mutants, Tiggrin is no longer O-glycosylated and fails to be properly secreted to the basal cell layer interface, resulting in disruption of proper cell adhesion. pgant3-mediated effects are dependent on the enzymatic activity of PGANT3 and cannot be rescued by another pgant family member, indicating a unique role for this glycosyltransferase. These results provide in vivo evidence for the role of O-glycosylation in the secretion of specific extracellular matrix proteins, which thereby influences the composition of the cellular 'microenvironment' and modulates cell adhesion events. The studies described in this review provide insight into the long-standing association between aberrant O-glycosylation and tumorigenesis, as changes in tumour environment and cell adhesion are hallmarks of cancer progression.